Translation, Cross-Cultural Adaptation, and Validation of the Kannada Version of the Exercise Adherence Rating Scale (EARS-Kn) Among Head and Neck Cancer (HNC) Survivors in a Tertiary Care Setup in India - Hritika D. Pai; K Vijaya Kumar; Prasanna Mithra; Stephen Rajan Samuel; Mariappan Senthiappan Athiyamaan; Emma Louise Godfrey (Integrative Cancer Therapies)
Background: Adherence in rehabilitation services includes attending appointments, regularly performing prescribed exercises, and correct exercise execution. The Exercise Adherence Rating Scale (EARS) has been adapted into several languages, but there is lack of a standardized tool for various Indian languages and cultural contexts, particularly for use with cancer survivors. With the anticipated 57.7% rise in cancer cases by 2040, this study aims to address this gap. Aims and objectives: To cross-culturally adapt EARS to Kannada (EARS-Kn) and evaluate its validity and reliability amongst HNC survivors enrolled in the Multimodal Oncology Rehabilitation Exercise—MORE © Program. Methodology: Following Beaton guidelines, the EARS tool was adapted to Kannada. 34 HNC survivors engaged in the MORE © program. Internal consistency (Cronbach’s ⍺) and construct validity (Exploratory Factor Analysis, EFA) were assessed. The Receiver Operating Curve (ROC) determined cut-off scores, sensitivity and specificity of the EARS-Kn. Results: The EARS-Kn demonstrated a Cronbach’s-⍺ value of .93. The EFA revealed a one-factor solution with eigenvalues exceeding one and 70.1% loading. The area under the curve (AUC) was 0.908. A cut-off score of 17 was established, with 95.83% sensitivity and 80% specificity. Conclusion: The EARS-Kn version showed strong validity and reliability among Kannada-speaking HNC survivors, indicating its potential to enhance the understanding of exercise adherence among them. Future studies could explore the EARS-Kn version among diverse populations prescribed various rehabilitation regimes. Studies could also further investigate psychometric properties of the EARS in different Indian languages among cancer survivors, which would help improve survivorship outcomes.